Power amplifier linearisation scheme to mitigate superfluous radiations and suppress adjacent channel interference - Varahram, Pooria; Mohd Ali, Borhanuddin; Mohammady, Somayeh; Sulaiman, Nasri (The Institution of Engineering and Technology, 2014)
Power amplifiers are one of the costly devices in wireless communication systems and exhibit non-linearity. The problem of non-linearity in the power amplifier categorises in two disturbance impacts, output distortion and in-band distortion which lead to adjacent channel interference and constellation deviation, respectively. In order to gain maximum efficiency of the power amplifier and reduce interference, the authors propose a new digital pre-distortion scheme called complex gain convergence (CGC). The proposed scheme is compared with indirect learning architecture and validated against an laterally diffused metal oxide semiconductor (LDMOS) power amplifier. The outcome of applying CGC scheme shows enhancement in adjacent channel leakage ratio and error vector magnitude performance while the complexity is even lower. An experimental demonstration with the actual power amplifier is also presented.